2018
DOI: 10.15208/beh.2018.65
|View full text |Cite
|
Sign up to set email alerts
|

Do financial development and personal remittances matter in South African economic growth? A bound testing investigation

Abstract: Do financial development and personal remittances matter in South African economic growth? | BEH: www.beh.pradec.eu -954 -Abstract: This study explores the relationship amongst financial development, remittances and the economic growth of South Africa using quarterly data spanning the period 1995Q01 to 2015Q04. The study used Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) techniques for the unit root test and the variables were found to be stationary at level and at first difference. Findings from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…While this result is in concord with the Grossman hypothesis, which views an individual as a producer and consumer of health, the longevity of such individuals could be endogenously determined. This result is in tandem with the work of [20] who noted that CO 2 emissions negatively impact human health in the region under investigation.…”
Section: Discussion Of Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…While this result is in concord with the Grossman hypothesis, which views an individual as a producer and consumer of health, the longevity of such individuals could be endogenously determined. This result is in tandem with the work of [20] who noted that CO 2 emissions negatively impact human health in the region under investigation.…”
Section: Discussion Of Resultssupporting
confidence: 85%
“…Empirical studies are divided into country-specific and crosscountry studies and investigations. For cross-sectional studies from 1990 to 2013, [20], for instance, engaged a quantile regression method to investigate the impact of environmental quality on an individual's health in the Anglophone countries of West Africa (Sierra Leone, Gambia, Ghana, Liberia, and Nigeria). Their findings revealed that CO 2 emissions from liquid and gaseous fuel consumption, public and commercial services, residential buildings, solid fuel consumption, and transport impacts negatively on human health in the subregion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abida and Sghaier (2014), in a study of 4 North African countries from 1980-2011, find that remittances positively impact economic growth, and also that the impact of remittances become more pronounced in the presence of financial development, an indication that financial development and remittances complement each other to influence growth. Olarewaju et al (2018), in a South African study from 1995 to 2015, employ ARDL on a quarterly data and find a positive and long-run relationship among financial development, remittances and economic growth, implying that a well-functioning financial system could increase remittance inflows and achieve economic growth in the long run. Abosedra and Fakih (2017) assess the role of remittances and financial deepening in Lebanon from 1993 to 2011.…”
Section: Literature Review 21 Theoretical Foundationmentioning
confidence: 99%